Compassion-Focused Therapy as an Intervention for Adult Survivors of Sexual Abuse. Issue 2 (17th February 2018) - McLean, Lisa; Steindl, Stanley R.; Bambling, Matthew
ABSTRACT: Child sexual abuse can have long-term negative impacts across psychological, physical, and interpersonal domains. Some of the common issues for survivors of sexual abuse include shame and self-blame, attachment-based difficulties, avoidant coping strategies, and reduced capacity for self-compassion. Compassion-focused therapy is a transdiagnostic intervention that specifically responds to these concerns. Compassion-focused therapy was originally developed for clients who experience high levels of shame and self-criticism and aims to strengthen the soothing and affiliative system through the cultivation of compassion. This article will highlight the theoretical alignment between some of the common issues and impacts associated with experiences of sexual abuse, with the core underlying principles of compassion-focused therapy. This includes (a) the capacity of the therapy's evolutionary framework to reduce perceptions of self-blame, (b) the cultivation of compassion to respond to feelings of shame, (c) acknowledgment of the role of early attachment experiences and facilitation of corrective affiliative experiences, (d) regulation of the threat-based system following trauma, and (e) provision of an alternative to avoidant-based coping by responding to distress with compassion. It is proposed that the theoretical framework and core focus and aims of compassion-focused therapy are highly applicable for survivors of sexual abuse and therefore holds significant promise as a treatment option for this client group.